Self-feeding urea-molasses and the feeding of Aureomycin to steer calves wintered on bluestem pasture - Smith, E.F.; Koch, B.A.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
The wintering phase of this trial has been reported previously in Circular 349. A self-fed urea-molasses mixture is being compared to molasses self-fed plus soybean oil meal in an effort to determine if a urea-molassess mixture self-fed on dry grass will serve as an adequate source of protein and energy. Another phase of the test is to determine if aureomycin will improve the performance of calves wintered on pasture without shelter.
Keywords: Cattle; Urea-molasses; Aureomycin; Bluestem pasture